Are we missing opportunities? Physiotherapy and physical activity promotion: a cross-sectional survey - Nicole Freene; Sophie Cools; Bernie Bissett (BMC, 2017)
Abstract Background Physical activity (PA) promotion in healthcare is an important strategy for increasing PA levels. Physiotherapists are well-positioned to promote PA, however no studies have investigated PA promotion by physiotherapists Australia-wide. Methods An online survey of practicing Australian physiotherapists was conducted to investigate knowledge of the Australian Physical Activity and Sedentary Behaviour (PASB) guidelines and factors associated with increased promotion frequency. Participants were asked to state the PASB guidelines and a 4-component scoring system was used to measure knowledge. Multivariate logistic regression analysis was conducted to assess factors associated with frequency of promotion. Results 257 Australian physiotherapists completed the survey. Only 10% were able to accurately state the PASB guidelines and 54% reported promoting PA to 10 or more patients per month. Males were nearly three times more likely than females to promote PA to 10 or more patients per month (OR 2.68, 95% CI 1.25-5.74). Those who lacked counselling skills and felt PA promotion wouldn't change their patients' behaviour were much less likely to promote PA. Conclusion Australian physiotherapists have poor knowledge of the Australian PASB guidelines and infrequently promote PA. Education and training in PA counselling and behaviour change strategies is indicated to enhance PA promotion by Australian physiotherapists.